Ventromedial hypothalamus relays chronic stress inputs and exerts bidirectional regulation on anxiety state and related sympathetic activity - Shao, Jie; Chen, Yan; Gao, Dashuang; Liu, Yunhui; Hu, Nan; Yin, Lianghong; Zhang, Xinzhou; Yang, Fan (Frontiers in Cellular Neuroscience, 2023)
Chronic stress can induce negative emotion states, including anxiety and depression, leading to sympathetic overactivation and disturbed physiological homeostasis in peripheral tissues. While anxiety-related neural circuitry integrates chronic stress information and modulates sympathetic nervous system (SNS) activity, the critical nodes linking anxiety and sympathetic activity still need to be clarified. In our previous study, we demonstrated that the ventromedial hypothalamus (VMH) is involved in integrating chronic stress inputs and exerting influence on sympathetic activity. However, the underlying synaptic and electrophysiological mechanisms remain elusive. In this study, we combined in vitro electrophysiological recordings, behavioral tests, optogenetic manipulations, and SNS activity analyses to explorestudy the role of VMH in linking anxiety emotion and peripheral SNS activity.Results showed that the VMH played an important role in bidirectionally regulating anxiety-like behavior and peripheral sympathetic excitation.Chronic stress enhanced excitatory inputs into VMH neurons by strengthening the connection with the paraventricular hypothalamus (PVN), hence promoting anxiety and sympathetic tone outflow, an important factor contributing to the development of metabolic imbalance 3 in peripheral tissues and cardiovascular diseases.